1999
DOI: 10.1152/jappl.1999.87.3.1178
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of exertional hyperthermia to sympathoadrenal-mediated lymphocyte subset redistribution

Abstract: The contribution of hyperthermia to the differential leukocytosis of exercise remains obscure. This study examined changes in circulating sympathoadrenal hormone concentrations and patterns of leukocyte and lymphocyte subset (CD3(+), CD4(+), CD8(+), CD19(+), CD3(-)16(+)/56(+)) redistribution during exercise, with and without a significant rise of rectal temperature (T(re)). Ten healthy men [age 26.9 +/- 5.7 (SD) yr, body mass 76.0 +/- 10.9 kg, body fat 13.9 +/- 4.6%, peak O(2) consumption: 48.0 +/- 12.4 ml x k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
58
5
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 50 publications
9
58
5
5
Order By: Relevance
“…As repeatedly shown following exercise (Foster et al 1986;Laing et al 2008;Rhind et al 1999) and hyperthermia (Brenner et al 1999;Kappel et al 1998;Walsh and Whitham 2006) interventions in AB populations, we report increased neutrophil, lymphocyte and monocyte numbers following hot water immersion. While increased neutrophil counts have been observed earlier following exercise interventions in CSCI populations, lymphocyte numbers remained unchanged in this population (Kouda et al 2012;Yamanaka et al 2010).…”
Section: Leukocyte Profilesupporting
confidence: 86%
See 1 more Smart Citation
“…As repeatedly shown following exercise (Foster et al 1986;Laing et al 2008;Rhind et al 1999) and hyperthermia (Brenner et al 1999;Kappel et al 1998;Walsh and Whitham 2006) interventions in AB populations, we report increased neutrophil, lymphocyte and monocyte numbers following hot water immersion. While increased neutrophil counts have been observed earlier following exercise interventions in CSCI populations, lymphocyte numbers remained unchanged in this population (Kouda et al 2012;Yamanaka et al 2010).…”
Section: Leukocyte Profilesupporting
confidence: 86%
“…In line with this, blocking β-adrenergic receptors in AB (Foster et al 1986) has been demonstrated to reduce the post-exercise increase in lymphocyte numbers. Similarly, exercise in cold water to keep core temperature constant results in a blunted adrenaline response in AB, causing a reduced increase in lymphocyte numbers following exercise (Rhind et al 1999). Finally, α-or β-adrenergic blockade in mice demonstrates the importance of adrenergic mechanisms for T cell migration following exercise (Kruger et al 2008).…”
Section: Leukocyte Profilementioning
confidence: 99%
“…Our observation that total leukocyte, granulocyte and lymphocyte counts rise in response to underwater cycle ergometer exercise is consistent with the findings reported by other investigators in our laboratory (23,82). Similarly, thermal clamping attenuated this leukocyte and granulocyte response.…”
Section: Effects Of Passive Heating and Moderate Exercise (With And Wsupporting
confidence: 93%
“…Animal studies further indicate that alpha adrenergic receptor-signalling pathways are involved in the increase of extracellular HSP70 (Johnson et al, 2005). Even though not directly measured in the current study, heat stress is associated with increases in sympathetic activity (Rhind et al, 1999;Starkie et al, 2005), which has been previously suggested to be a mechanism modulating immune responses (Rhind et al, 1999). The differences in the heart rate or ratings of perceived exertion between conditions indicate that INT was the more stressful condition that could be associated with increased sympathetic activity, which would further explain the difference in HSP70 elevations found between conditions.…”
Section: Discussionmentioning
confidence: 58%